Association between the ACE I/D polymorphism and muscle injuries in Italian and Japanese elite football players - Massidda, M.; Miyamoto-Mikami, E.; Kumagai, H.; Ikeda, H.; Shimasaki, Y.; Yoshimura, M.; Cugia, P.; Piras, F.; Scorcu, M.; Kikuchi, N.; Calò, C. M.; Fuku, N. (Journal of Sports Sciences, 2020)
ACE I/D polymorphism has been recently associated with the susceptibility to inflammation and muscle damage after exercise. The aim of this study was to understand the association between the ACE I/D polymorphism and muscle injuries in a large cohort of elite football players from two different countries. Seven hundred and ten male elite football players from Italy (n = 341) and Japan (n = 369) were recruited for the study. Genomic DNA was extracted from either the buccal epithelium or saliva using a standard protocol. Structural-mechanical injuries and functional muscle disorders were recorded from 2009 to 2018. A meta-analysis was performed using Review Manager 5.3.5. In the Japanese cohort, the ACE I/D polymorphism was significantly associated with muscle injury using the D-dominant model (OR: 0.48, 95% CI: 0.24-0.97, P = 0.040). The meta-analysis showed that in the pooled model (Italian and Japanese populations), the frequencies of the DD+ID genotypes were significantly lower in the injured groups than in non-injured groups (OR: 0.61, 95% CI: 0.38-0.98, P = 0.04) with a low degree of heterogeneity (I2 = 0%). Our findings suggest that the ACE I/D polymorphism could influence the susceptibility to developing muscle injuries among football players.